Implications of Toppling Goal Posts in College Football: Managing Institutional Risk - David LaVetter; Yun Seok Choi (Journal of Applied Sports Management, 2010)
This article discusses a summary of lawsuits stemming from fans being injured by toppled goal posts following American college football games. Several examples of goal post-related injuries occurred during post-game celebrations when crowds surged onto the fields at various stadiums. The purpose of this article is to explicate the legal implications of lawsuits filed by injured plaintiffs and discusses potential liability incurred by educational institutions. Very limited legal precedence exists to facilitate understanding of the full legal responsibilities of injured individuals, institutions, parties providing security, or goal post manufacturers; however, courts have ruled on three particular cases involving injuries sustained by toppled goal posts. Administrative insights are sorely needed to provide better understanding of associated risks and potential liabilities arising from goal post-related injuries occurring on American college campuses in the U.S., including modifications of current practices to minimize spectator injuries and institutional liabilities, specifically as related to increased security measures, proper warnings, collapsible goal post structures, imposed fines, and state legislation.
Keywords: Goal posts; Liability; Risk; Injuries; Negligence; College Football; Intercollegiate Athletics; Sport Law; Stadium Security; Crowd Control; Event Management; Facility Management